OVERVIEW OF RENEWABLE ENERGY SOURCES IN THE PERSPECTIVE OF CARBON FOOT PRINTING REDUCTION - DR. ANWAR M. MULLA (International Journal of Innovations in Engineering Research and Technology, 2021)
A review is done on the different methods to reduce the carbon emission ultimately the carbon footprint in the different sectors in the perceptive of the renewable sources. In method for the Regional energy targeting along with the supply chain synthesis different algorithms are proposed such as Regional Energy Clustering (REC) for the biomass supply chains. Some method as are based on the scheduling the manufacturing processes in process industries so as to reduce the carbon footprint and energy consumption.